Characteristics of Eucheuma denticulatum and Turbinaria conoides porridge as body lotion materials - Nurjanah; Nurilmala, M.; Abdullah, A.; Seulalae, A. V.; Fauzan, R. (International Journal of Agricultural Technology, 2021)
Utilization of seaweed is driven by increasing seaweed production every year. Red algae and brown algae are the seaweeds that widely used in Indonesia. The characteristics, antioxidant activity and get the best combination of Eucheuma denticulatum and Turbinaria conoides seaweed porridge as body lotion materials were determined. The combination ratios of E.denticulatum and T.conoides were 1:1, 1:2, and 2:1, respectively. The best combination seaweed porridge of E. denticulatum and T. conoides found in ratio 1:2 with IC50 value was 173.72 mg/L, and total phenol was 455 mgGAE/g. IC50 and Loss on Drying (LoD) in lotion product was 280.17 mg/L and 82.47%, respectively. The sensory test results were neutral so that seaweed porridge can be used as raw materials of lotion